A geopolymer route to micro- and meso-porous carbon. Issue 12 (13th February 2020) - Pei, Yi-Rong; Yang, Jae-Hun; Choi, Goeun; Choy, Jin-Ho
Abstract : We report the synthesis of microporous carbon through a geopolymer route starting from natural clay kaolinite. Abstract : Hexagonal and wormhole-type mesoporous geopolymers were developed by controlling the concentration of a structure directing agent (cetrimonium bromide, CTAB) with fixed ratios of Si/Al, KOH/(Si + Al), and H2 O/(Si + Al), and their detailed porous structures were confirmed by TEM, N2 adsorption–desorption and X-ray diffraction measurements. The as-prepared geopolymers were then used as templates to replicate porous carbons with various structures and porosities for CO2 adsorption. To understand the correlation between the CO2 adsorptivity and porous structures, we tuned the porosity of the geopolymer-templated carbons by modifying the structures of the geopolymers. The porous carbons obtained from the hexagonal-type porous geopolymers were found to be composed of the aggregates of carbon nanowires exhibiting large particles, while those obtained from the wormhole-like porous geopolymers were determined to be wormhole type as well, as evidenced by TEM and X-ray diffraction studies. According to the CO2 adsorption isotherms of the porous carbons, the aggregates of carbon nanowires exhibited the highest CO2 adsorptivity due to their highest microporosity and largest specific surface area.